Stokes parameters of optical singularities of random electromagnetic beams - 李建龙 朱世富 (Chinese physics B, 2010)
In this paper, the relation between the spectral degree of coherence and degree of polarization of random electromagnetic beams is derived by the Stokes parameters. And the concept of polarization singularity is extended from spatially fully coherent beams to partially coherent electromagnetic beams. Theoretical analysis shows that correlation vortices are linearly polarized singularities. The results are illustrated by numerical examples.